Metabolome and beef quality from Nellore cull cows as affected by days on feedlot or by dry or wet ageing - Miguel Estrada, Mauricio (2018)
The present work was based on two experiments. The objective of first experiment was to evaluate the metabolome and beef quality of zebu cull cows, slaughtered after three different periods of feedlot. A total of 20 Nellore cull cows, with an average age of 10.6 years (standard deviation, SD 2.5), fed with Brachiaria decumbens grass without supplementation two months before beginning the experiment were used. At the beginning of the experiment, the animals were weighed and wormed. The animals presented 442.4 kg (SD ± 41.6) of initial SBW, 55.87 cm 2 of REA and 4.23 mm of SFT. The animals were randomly assigned in three treatments: six cows slaughtered at the beginning as control group (C0), seven confined for 28 days (C28) and seven for 58 days (C58). The C28 and C56 treatments were fed with a feedlot diet according to the nutrients requirements for non-pregnant dry beef cows of BR-CORTE, aiming at an average daily gain of 1.2 kg. At the end of each experimental period, the animals were slaughtered and a sample of the Longissimus lumborum muscle was immediately obtained for metabolite analysis. Subsequently, after 24 hours of carcass cooling, six one-inch steaks of the same muscle were obtained for meat quality analyzes, being two steaks randomly distributed in three ageing times (0, 7, and 14 days). Performance data, carcass characteristics and meat quality were analyzed using the SAS GLM procedure, using weight and initial age as covariates; while metabolites in muscle and meat were analyzed by the TruTOF GC-MS system. Muscle of C28 and C56 showed a higher concentration of sugars (glucose, fructose and glycerol) and amino acids (leucine, alanine, isoleucine, valine, aspartate). The tenderness of the meat increased with the days in feedlot (P=0.0305) and aging time (P<0.0001). It is concluded that the feedlot increases the fatness of the cull cow ́s carcass, which is reflected in a slow temperature drop and fast pH decline, improving the qualitative characteristics of the meat. The second experiment aimed to determine the metabolomic and the beef characteristics of cull Nellore cows from the grazing system, subjected or not to two different ageing techniques (Dry-aged versus Wet-aged) for 14 days, using analysis traditional as well as modern techniques to identify major changes in the metabolic profile of meat. For this, twelve carcasses of cull Nellore cows were used. Of each carcass, two sections were collected between the 9th and 11th ribs, one of each half carcass, and randomly designated for one of the aging treatments (Dry-aged or Wed- aged). In addition, two Longissimus lumborum muscle steaks were removed immediately bellow the 11th rib as the treatments without aging (WA). Dry-aged samples were aged without any packaging in direct contact with the cooling room environment, while the Wet-aged samples were vacuum packed in plastic bags. The samples were aged for 14 continuous days at 4 °C and 85% humidity. The experimental design was completely randomized and the data analyzed using the SAS GLM procedure. It was determined that aging reduced the shear force (P < 0.0001) and increased metabolites such as amino acids, sugars and lipids, without differences between treatments. Dry-aged beef present greater losses (P < 0.0001) causing lower total salable yield. Whiles Wet samples have a higher concentration (P = 0.01445) of biogenic amines (e.g. Putrescine) which would reduce its shelf life. It is concluded that aging of cull cow beef is a viable option to improve the physicochemical characteristics of the product.